LOCAL ECONOMIC DEVELOPMENT INDEX FOR BRAZILIAN MUNICIPALITIES/ÍNDICE DE DESENVOLVIMENTO ECONÔMICO LOCAL PARA MUNICÍPIOS BRASILEIROS - Renzi, Adriano; Piacenti, Carlos Alberto (Informe GEPEC, 2022)
The article aims to constitute a new index capable of measuring Brazilian municipalities' level of economic development. A set of variables were chosen, partly representing the economic, social, demographic, and environmental dimensions, observing the municipalities' local and rural aspects. This index was conceived through factor analysis (principal component), with data from the IBGE[1] Agricultural and Demographic Census, IPEADATA, DATASUS, the Human Development Atlas of Brazil, and it provides an alternative to the HDI-M and IFDM-G, complementing them, to explain the inequality gap between Brazilian Regions with greater reliability. O artigo objetiva constituir um novo índice capaz de medir o nível de desenvolvimento econômico dos municípios brasileiros. Foi escolhido um conjunto de variáveis, representando em parte as dimensões econômica, social, demográfica e ambiental, observando os aspectos rurais e locais dos municípios. Este índice foi concebido por meio de análise fatorial (componente principal), com dados do Censo Agrícola e Demográfico do IBGE, IPEADATA, DATASUS, o Atlas do Desenvolvimento Humano do Brasil, e fornece uma alternativa ao IDH-M e ao IFDM-G, complementando-os, para explicar o hiato de desigualdade entre as regiões brasileiras com maior fidedignidade.